Advances in spermatogonial stem cell research: A systematic review and bibliometric analysis - Mohammed, Nur Hafizah; Shikhmaidin, Mashitah (UMK Press, 2025)
Spermatogonial stem cells (SSC) are an exceptionally rare group of testicular cells that give rise to all subsequent male germ cells, the basis of spermatogenesis and male fertility. The SSC have shown great potential in livestock breeding systems, medical applications, and genetic conservation of endangered species. In this study, we used bibliometric analysis to assess worldwide research trends in the SSC area based on publication outputs, co-authorships among authors, and affiliated countries. A systematic review was performed to discuss: 1) The culture system of SSC, 2) The methods used to generate an ideal male for SSC transplantation, 3) The type of transplantation and the success of SSC transplantation in various species, 4) Application of SSC culture and transplantation technique to agricultural practice. Results of the bibliometric analysis on the Scopus database showed a total of 2171 research articles issued between 1965 to 2023. With a consistent annual publication of more than 100 articles, it was suggested that a strong interest in SSC research started in the last 11 years. About 54% of the total global publications were contributed by researchers from the United States of America (USA) and China, leading the other 59 countries/territories. The three main topics in SSC research are the culture system, generation of an ideal male recipient, and SSC transplantation applications. The culture system has the highest number of publications, reflecting its importance in studying and manipulating SSC. Currently, several challenges must be addressed before this technique can be applied in agricultural contexts, particularly the establishment of a stable long-term culture system. Looking ahead, we anticipate ongoing development and optimization of the SSC culture system and its application in the field, which will enhance valuable approaches for improving livestock production.